Uji Hedonik Seduhan Jamu Saintifik Antihipertensi pada Lansia di RSUD Wates Kabupaten Kulon Progo - Heryanto, Catharina Apriyani Wuryaningsih; Permanasari, Prisci Permanasari; Hartanto, Fajar Agung Dwi; Dian Purwitasari; Mahardika, Andhika (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Scientific herbal medicine has long been utilized by the public to address various health conditions, including hypertension. The practice of prescribing scientific herbal medicine has also been implemented in several herbal clinics, such as the Hortus Medicus clinic, though it is primarily limited to the local community around Tawangmangu. Given the growing interest in scientific herbal medicine, this study, in collaboration with industry partners, aimed to develop an antihypertensive herbal tea. The primary objective of this research was to conduct a hedonic test of the antihypertensive tea among the elderly population. The initial step involved assessing the preference for this antihypertensive tea among elderly patients at Wates Regional Hospital. The hedonic test evaluated respondents' reactions to the product's taste, color, aroma, and appearance. The results from 48 elderly respondents indicated a positive response, with a 62.5% preference for taste, 77.8% for aroma, and 100% for both color and appearance. In conclusion, all parameters were well-accepted by the majority of respondents, and further development of the product for commercial use is recommended.